Analisis Sosiologi Sastra Novel “Kembali” Karya Sofia Mafaza - Perdana, Adhi Dian (Kajian Bahasa dan Sastra (KABASTRA), 2024)
As social creatures, we must be able to interact socially well with this easy-to-access environment and era. The author is interested in analyzing the novel Back because the novel is very interesting and the storyline that is presented is closely related to students and a social life that is often found in everyday life. This study aims to appreciate literature by reading, studying, enjoying the storyline and analyzing a novel titled Back by Sofia Mafaza. This study uses descriptive qualitative methods, using the study of literary sociology and intrinsic elements. Sociology as a study of literary works related to how one can interact with the surrounding environment. In the research sociology of literature study discusses 1). Sociology of authors 2). Social Condition 3). Social conditions of society 4). Religious values 5). Social society 6) Social culture 7). Intergovernmental social learning and students 8). Educational Value. From the results analyzed using descriptive qualitative methods, this novel discusses the main characters who can interact well between characters. Social interactions in the novel include mutual cooperation, social service, cooperation, meetings and counseling between siblings and siblings.